2001
DOI: 10.1103/physreve.63.026103
|View full text |Cite
|
Sign up to set email alerts
|

Scaling behavior for finite O(n) systems with long-range interaction

Abstract: A detailed investigation of the scaling properties of the fully finite O(n) systems, under periodic boundary conditions, with long-range interaction, decaying algebraically with the interparticle distance r like r(-d-sigma), below their upper critical dimension, is presented. The computation of the scaling functions is done to one loop order in the nonzero modes. The results are obtained in an expansion of powers of sqrt[epsilon], where epsilon=2sigma-d up to O(epsilon(3/2)). The thermodynamic functions are fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 35 publications
6
34
0
Order By: Relevance
“…The function F d,σ (y) is well known [2] in the theory of FSS. Finally, let us notice that one can easily see that the expression (6) for z as a function of y verifies the FSS hypotheses and, consequently, all the thermodynamic functions, which indeed are z dependent, do [45]. At the critical temperature T c (i.e.…”
Section: Binder's Cumulantsupporting
confidence: 54%
See 4 more Smart Citations
“…The function F d,σ (y) is well known [2] in the theory of FSS. Finally, let us notice that one can easily see that the expression (6) for z as a function of y verifies the FSS hypotheses and, consequently, all the thermodynamic functions, which indeed are z dependent, do [45]. At the critical temperature T c (i.e.…”
Section: Binder's Cumulantsupporting
confidence: 54%
“…It has been found that the scaling properties of the system with SR interaction remains valid also in the case of LR interaction (for a review see e.g Chapters 4 and 5 in [2] and references therein). For finite n a limited number of recent numerical results [30,32,34], as well as few analytical works [32,34,44,45,46] became available.…”
Section: Leading Lr Interactionmentioning
confidence: 99%
See 3 more Smart Citations